Treatment of proximal tibia fractures with locking compression plate: a prospective study - Kommuru, Devendra V.; Singh, Shikhar; Shetty, Sunil; Kale, Sachin; Srivastava, Abhilash (International Journal of Research in Orthopaedics, 2022)
Background: With the rise in the incidence of proximal tibia fractures in India due to road traffic accidents, this prospective study was intended to assess the operative procedure in the management of such fractures using the locking compression plate (LCP).Methods: 30 subjects attending the study site scheduled to undergo the defined surgery were enrolled as per the study selection criteria.Results: A total of 30 patients with proximal tibia fractures were enrolled. Majority of cases were due to RTAs, with a higher incidence of types IV, V and VI. Average time for union of fracture ranged from around 16-24 weeks. 23 patients were treated with ORIF and 7 patients were treated with MIPO technique. Three different principles of fixation were done using the LCP, viz. compression, bridging and combined. Functional outcome was evaluated, which revealed excellent results in 53.33% patients, good results in 30% patients, fair results in 13.33% results, while 3.33% had poor outcomes.Conclusions: Based on the findings of the present study we can conclude that overall Locking Compression plate (LCP) for fractures of the proximal tibia is a useful adjunct in the management of trauma patients. The locking compression plate system with its various type of fixation act as a good biological fixation including difficult fracture situations.